(untitled) (Jurnal Ilmu Manajemen dan Bisnis, 2021)
The objectives of this study were: 1) To determine the effect of discipline on the productivity of teaching staff and teaching staff at SMPNs in Paguyaman District; 2) To determine the effect of the work environment on the productivity of teaching staff and education personnel at SMPNs in Paguyaman District; 3) To determine the effect of discipline and work environment on the productivity of teachers and education personnel at SMPNs in Paguyaman District. This research uses quantitative methods. Sources of data in this study are primary data which is carried out using questionnaires. The data analysis technique used is multiple regression analysis using the SPSS version 21 program. The results showed that (1) The work environment has a positive and significant effect on teacher productivity in State Junior High Schools (SMP) throughout Paguyaman District, Boalemo Regency with a determinant value of 19.50%. The meaning of the positive coefficient shows that the work environment has a good impact in increasing teacher productivity in State Junior High Schools (SMP) throughout Paguyaman District, Boalemo Regency. (2) Work discipline has a positive and significant effect on teacher productivity in State Junior High Schools (SMP) throughout Paguyaman District, Boalemo Regency with a determinant value of 58.10%. The meaning of the positive coefficient shows that the better the work discipline of the teacher in fulfilling the mandated duties and responsibilities, the productivity of teachers in State Junior High Schools (SMP) throughout Paguyaman District, Boalemo Regency will be more optimal as well. (3) Work environment and work discipline together have a positive and significant effect on teacher productivity in State Junior High Schools (SMP) in Paguyaman District, Boalemo Regency with a determinant value of 77.60%. While the remaining 22.40% can be explained by other variables not examined in this study such as leadership, compensation, job placement, organizational culture, work stress, training, teacher commitment and other variables